FORMULASI MEDIA PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq.) P. Kumm.) BERBAHAN DASAR DEDAK PADI DAN LIMBAH KOPI - Umrah, Umrah; Triana, Nina Risnanda; Yuniati, Eny; Kasim, Amiruddin; Zainal, Amalia Purnamasari (Biocelebes, 2024)
Rice bran and coffee waste as a medium and source of nutrients needed for the growth of the white oyster mushroom mycelium (Pleurotus ostreatus (Jacq.) Kumm.). This research has been carried out at Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. This study has almed : (1) To determine the growth of white oyster mushrooms (P. ostreatus (Jacq.) Kumm.) in the formulation of rice bran and coffee waste media. (2) Knowing the ratio in the media formulation of rice bran waste and coffee waste that can provide the best growth of white oyster mushroom (P.ostreatus (Jacq.) Kumm.). Data analysis research used in a completely randomized design (CRD), consisting of seven treatments and three replications, namely P1 (100% rice bran), P2 (95% rice bran + 5% coffee waste powder), P3 (90% rice bran + 10% coffee waste powder), P4 (85% rice bran + 15% coffee waste powder), P5 (80% rice bran + 20% coffee waste powder), P6 (75% rice bran + 25% coffee waste powder), P7 (sawdust 70% + rice bran 20% + corn flour 10% (positive control). The results showed that the best mycelium of growth were P7 and P1. The highest number of colonies were at treatment P7 1,26x1012CFU/gr and the lowest was P1 0,26x1012CFU/gr. The fastest incubation time was found in P7, which was 25 days and the lowest was in treatment was P6, 48 days.